The Figurative Languages on Disney Encanto Original Soundtrack Album - A’innaya Zahra Chusnul Chotimah; I Nyoman Sedeng; I Gusti Ngurah Parthama (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This research is entitled "The Figurative Languages on Disney Encanto Original Soundtrack Album." This study presents the lyrics of seven songs in the Encanto album based on how each lyric holds figurative language. The data source of this research was primarily taken from one soundtrack album from the Encanto movie. The documentation method was used to process the research data and analyze it using figurative language types (Abrams, 1999). The results show 17 types of figurative language were found they are an allegory, allusion, alliteration, ambiguity, antithesis, metaphor, pun, paradox, personification, irony, imagery, metonymy, hyperbole, synecdoche, simile, understatement, and onomatopoeia.